Монгол улсад төвлөрлийг сааруулах асуудал - Л, Энхтайван; Л, Ариунаа (Proceedings of the Mongolian Academy of Sciences, 2017)
No Mongolian Abstract In general decentralization is connected with the transfer of responsibilities for planning, management, resource raising and allocation from the central government to the lower levels of government. In particular fiscal decentralization means that local authorities become responsible for the expenditure and revenue assignment. From the economic and political science perspectives fiscal decentralization will improve resource allocation and accountability, which results in an efficient and effective supply of public goods and support private markets. In last decade Mongolia has introduced a number of decentralization measures, which followed a top dawn approach and were slowly implemented without any integrated decentralization strategy. Currently Mongolia is a de-concentrated state with fiscal centralization. The local governments are still far away from having the political, administrative and fiscal autonomy to manage their own affairs.